Entanglement and area laws in weakly correlated gaussian states - Matera, Juan Mauricio (2012)
In the next slides we will see how the picture of the relationship between entanglement, correlations and influence of the environment.also give us a geometrical intuition about the entanglement of subsystems: the emergence of area laws. [Extracto a modo de resumen]